DETERMINANTS OF IMPLEMENTATION OF OHS CULTURE AT RSIA BUNDA CIPUTAT, SOUTH TANGERANG CITY, IN 2022 - Hadis Akbari; Munaya Fauziah; Agus Triyono (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The hospital is one of the workplaces that has a high risk of danger that can cause accidents or work-related illnesses. The application of OSH culture in hospitals is needed to minimize incidents of accidents and work-related illnesses by hospital standards or targets to achieve zero accidents. Purpose: The purpose of this research is to find out the determinants of implementing OSH culture at RSIA Bunda Ciputat in 2022. This quantitative observational study used an analytic survey with a cross-sectional approach. The sampling technique used a total sampling of 118 workers, which was carried out in December 2022 at RSIA Bunda Ciputat. Data analysis with logistic regression (=0.05). The application of OSH culture at RSIA Bunda Ciputat is not optimal; only 40.7% of respondents applied well, and 59.3% did not do well. Leadership and attitude simultaneously affect the application of OSH culture after being controlled by perception and action variables (p = 0.00). The most dominant factor in implementing OSH culture is leadership (p = 0.011, B = 1.999, OR = 3.001). There are 4 factors (leadership, attitude, perception, and action) that influence the application of OSH culture at RSIA Bunda Ciputat, and 2 factors, including perception and action, are confounding factors. Suggestion: One of the strategies needed to increase the application of an occupational health and safety culture in hospitals is to optimize the functions of the occupational health and safety committee, supervision, and training related to worker health and safety.